Natural deep eutectic solvent-ultrasound assisted extraction: A green approach for ellagic acid extraction from Geum japonicum - Yang, Zhao; Yue, Shi-Jun; Gao, Huan; Zhang, Qiao; Xu, Ding-Qiao; Zhou, Jing; Li, Jia-Jia; Tang, Yu-Ping (Frontiers in Nutrition, 2023)
In China and other Asian nations, Geum japonicum (GJ) is used as functional vegetables or as a type of folk medicine. Ellagic acid (EA) is one of the main active ingredients in GJ and has been utilized in food, cosmetics, and medicinal goods worldwide. Natural deep eutectic solvents (NADESs) have gradually replaced organic solvents for efficient extraction of plant-derived active compounds due to its environmental protection, low toxicity, low solubility, reusability, etc. In this work, several NADESs were tailored for the ultrasound assisted extraction (UAE) of EA from GJ, among which choline chloride-oxalic acid (ChCl:Oa) was the most effective. In optimal conditions, ChCl:Oa extract produced higher EA yields than common organic solvents including methanol, ethanol and acetone. In vitro antioxidant experiments showed that ChCl:Oa extract had stronger DPPH radical scavenging ability than other solvent extracts. Mechanically, Fourier transform infrared (FT-IR) results indicated that ChCl:Oa could form a hydrogen bonding with EA, which enhanced the stability of EA. Meanwhile, ChCl:Oa-UAE treatment could destroy the tissue structure of GJ, thereby improving EA yield. In conclusion, these results imply that the ChCl:Oa-UAE method might be an environmentally friendly approach for extracting EA from GJ.